Partial Hydrogenation of Calophyllum Inophyllum Methyl Esters to Increase the Oxidation Stability - Joelianingsih Joelianingsih; P. Putra; A.W. Hidayat; R. Fajar (Journal of Engineering and Technological Sciences, 2015)
Calophyllum inophyllum methyl esters have a low oxidation stability value (5-6 h) caused by high amounts of polyunsaturated fatty acid methyl esters (FAME), especially methyl linoleate. Partial hydrogenation was done to reduce the number of polyunsaturated FAME to transform them into mono-unsaturated. This was performed at 6 bar and 900 rpm with Pd/Al2O3 solid catalyst in a reactor with a capacity of 1 liter. The research purpose was to learn the effects of reaction temperature (80; 100; 120°C) and time (1; 1.5; 2 h) on the FAME composition. The optimum condition of the experiment was obtained at 120°C for 1 h, with 15.47 h as the oxidation stability value, 17.8°C as the cloud point value, and 51.17 as the cetane number. Under this condition, the methyl linoleate content decreased by 59.89% w/w (from 21.869% to 8,770% w/w) and methyllinoleate hydrogenated into methyl elaidate. Meanwhile, the methyl linolenate content decreased by 85,37% w/w (from 0.205% to 0.030% w/w) and methyl linolenate hydrogenated into methyl linolelaidate. These results show that the research met the following standards: a minimum oxidation stability value of 10 h in accordance with the World Wide Fuel Charter (WWFC) 2009, a maximum cloud point value of 18°C and a minimum cetane number 51 in accordance with SNI 7182-2012. The physical properties values of the Calophyllum inophyllum methyl esters were predicted using the empirical equations.